Carbonized Cow Dung as a High Performance and Low Cost Anode Material for Bioelectrochemical Systems - Feng, Huajun; Ge, Zhipeng; Chen, Wei; Wang, Jing; Shen, Dongsheng; Jia, Yufeng; Qiao, Hua; Ying, Xianbin; Zhang, Xueqin; Wang, Meizhen (Frontiers in Microbiology, 2018)
We report an efficient way to convert cow dung (CD) into a high-performance anode material for bioelectrochemical systems through a heat-treatment in a nitrogen atmosphere. Thermal gravimetric analysis showed that the CD carbonization process started at 300 °C and ended at approximately 550 °C; the weight was reduced by 51%. After a heat-treatment at 800 °C for 2 h, the treated CD featured a good conductivity and a high surface area. The maximum current density achieved for a CD anode (heated at 800 °C) was 11.74 ± 0.41 A m-2, which was approximately 2.2 times as high as that of commonly used graphite felt anodes (5.50 ± 0.10 A m−2). This study shows that a value-added anode material can be produced through conversion of CD by high-temperature carbonization. This approach provides a new way to alleviate environmental problems associated with CD.